2007
DOI: 10.1111/j.1096-0031.2007.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetic evaluation of Leandra (Miconieae, Melastomataceae): a polyphyletic genus where the seeds tell the story, not the petals

Abstract: Melastomataceae is a tropical family of 4500–5000 species divided into nine tribes. The largest tribe, Miconieae, is composed of approximately 2200 species in 30 genera and is found exclusively in the Neotropics. Previous phylogenetic analyses of the Miconieae have suggested that many of the genera are derived from a paraphyletic Miconia. However, these analyses only included six species of the large genus Leandra, so its phylogenetic affinities remained unclear. As currently defined Leandra is characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 27 publications
6
55
0
9
Order By: Relevance
“…The position of the inflorescence was considered diagnostic for these sections (terminal in Oxymeris and transitioning from terminal to lateral in Chaetodon), but this character is highly variable among some species and not always evident on herbarium sheets lacking either flowering or fruiting material. Phylogenetic analyses showed that these sections are not monophyletic as previously discussed (Martin et al 2008), confirming that this character is homoplastic. The types of L. nutans and L. urophylla share with L. acutiflora sparse, deciduous, minute dendritic trichomes, and leaves distinctly plinerved bearing white tufted domatia on the axils of the lateral nerves on the abaxial surface.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…The position of the inflorescence was considered diagnostic for these sections (terminal in Oxymeris and transitioning from terminal to lateral in Chaetodon), but this character is highly variable among some species and not always evident on herbarium sheets lacking either flowering or fruiting material. Phylogenetic analyses showed that these sections are not monophyletic as previously discussed (Martin et al 2008), confirming that this character is homoplastic. The types of L. nutans and L. urophylla share with L. acutiflora sparse, deciduous, minute dendritic trichomes, and leaves distinctly plinerved bearing white tufted domatia on the axils of the lateral nerves on the abaxial surface.…”
Section: Resultssupporting
confidence: 55%
“…Inflorescence position is one of the two characters traditionally used to circumscribe genera in the tribe Miconieae and great taxonomic importance has historically been placed on this character. Nonetheless, it has been demonstrated to be either prone to miscoding (Judd & Skean 1991) or to be highly homoplastic (Michelangeli et al 2004, Martin et al 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the whole genus seems to be polyphyletic, most of the species fall into three distinct clades. One of them (Leandra 'sensu stricto') includes almost all species of the genus occurring in eastern Brazil, plus some species previously described in the genera Ossaea DC., Clidemia D.Don, and all Pleiochiton A.Gray, also from eastern Brazil (Michelangeli et al 2004, Martin et al 2008. The species in this group have shrubby habit, non-scorpioid inflorescences, narrow petals and unappendaged seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Leandra Raddi is a genus with c. 250 species, all restricted to the Neotropics (Martin et al 2008). While the whole genus seems to be polyphyletic, most of the species fall into three distinct clades.…”
Section: Introductionmentioning
confidence: 99%